2000
DOI: 10.1007/s003740000233
|View full text |Cite
|
Sign up to set email alerts
|

Within-field variability of mineral nitrogen in grassland

Abstract: The within-field variability of soil mineral nitrogen (N-min) in a grazed grassland of 8000 m(2) was examined. NO3--N concentrations were characterized by a high spatial variability. This can be explained by the uneven deposition of animal excreta. All NH4+-N as well as NO3--N values were lognormally distributed, be fore and after the grazing season. At the end of the grazing season the largest part of the variability of NO3--N was found for NO3--N concentrations measured within a distance of a few metres. A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…These results contrast with similar studies performed on arable soils, which were characterised by ranges of spatial dependencies for NO 3 À of greater than 39 m (van Meirvenne et al, 2003;Haberle et al, 2004). The observed variation at larger spatial-scales, especially NO 3 À , could be due to the habit of sheep to frequent certain areas of the pasture such as paths, a drinking trough and areas of shade (Bogaert et al, 2000).…”
Section: Spatial Variation Of Soluble N At Within-field Scalescontrasting
confidence: 84%
See 2 more Smart Citations
“…These results contrast with similar studies performed on arable soils, which were characterised by ranges of spatial dependencies for NO 3 À of greater than 39 m (van Meirvenne et al, 2003;Haberle et al, 2004). The observed variation at larger spatial-scales, especially NO 3 À , could be due to the habit of sheep to frequent certain areas of the pasture such as paths, a drinking trough and areas of shade (Bogaert et al, 2000).…”
Section: Spatial Variation Of Soluble N At Within-field Scalescontrasting
confidence: 84%
“…The proportion of the total accumulated variance attributed to the 1-cm scale was much larger for amino acid-N and NH 4 + -N than NO 3 -N which may be related to their relative diffusion coefficients, interactions with the solid phase (Owen and Jones, 2001) and the rapid rate of amino acid turnover and mineralisation in this soil (Jones et al, 2004;Wilkinson et al, 2014). Similar small-scale variation of NO 3 À in grazed pastures has been identified in previous studies, with semi-variograms exhibiting the range of spatial dependency of less than 5 m (White et al, 1987;Broeke et al, 1996;Wade et al, 1996;Bogaert et al, 2000), and a nugget variance of 60% (Bogaert et al, 2000). These results contrast with similar studies performed on arable soils, which were characterised by ranges of spatial dependencies for NO 3 À of greater than 39 m (van Meirvenne et al, 2003;Haberle et al, 2004).…”
Section: Spatial Variation Of Soluble N At Within-field Scalessupporting
confidence: 52%
See 1 more Smart Citation
“…When splitting the data set, the data was strongly skewed: the N t and C org data of the mineral soil samples (C org < 15%) was right-skewed, while the data of the organic soil samples (C org > 15%) was left-skewed. Logarithmic transformation of the subset 'mineral soil' led to a normal distribution, which is typical for many properties of mineral soils (Bogaert et al, 2000;Cambardella et al, 1994). In transect A and B, the soil samples (N t and C org ) were also distributed bimodally, and splitting the data set showed that the data of the mineral subset was rightskewed, while the subset 'organic soil' was left-skewed (Tables 4 and 5).…”
Section: Soils and Soil Propertiesmentioning
confidence: 99%
“…(2) above were chosen based on reported variation coefficients (in percent) for denitrification, nitrate content, water-filled pore space and soil temperature (e.g., Christensen et al, 1990;Clemens et al, 1999;Luo et al, 1999;Rö ver and Kaiser, 1999;Rö ver et al, 1999;Bogaert et al, 2000;Luo et al, 2000;Yanai et al, 2003); i.e., denitrification in range [6%-1677%], N in range [11%-256%], S in range [6%-11%], and for T one value was reported, namely, 4%. Thus, errors in S and T are relatively small, while those for N and D r are relatively large.…”
Section: Effect Of Measurement Errorsmentioning
confidence: 99%